2014
DOI: 10.1097/shk.0000000000000074
|View full text |Cite
|
Sign up to set email alerts
|

Creating a Prosurvival Phenotype Through a Histone Deacetylase Inhibitor in a Lethal Two-Hit Model

Abstract: Objectives Hemorrhagic shock (HS) can initiate an exaggerated systemic inflammatory response and multiple organ failure, especially if followed by a subsequent inflammatory insult (“second hit”). We have recently shown that histone deacetylase inhibitors can improve survival in rodent models of HS or septic shock, individually. In the present study, we examined whether valproic acid (VPA), a histone deacetylase inhibitor, could prolong survival in a rodent “two-hit” model: HS followed by septic shock from ceca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 26 publications
(43 reference statements)
3
20
0
Order By: Relevance
“…Importantly, these results were achieved in the absence of standard fluid resuscitation. Similar benefits were seen in a “two-hit” models, where hemorrhage was followed by a CLP insult in rodents (56). In that study, rats treated with VPA showed a significantly better long-term survival rate (86% vs. 14%, p < 0.05) (Figure 3a), suppressed inflammatory profile (Figure 3b), and lower severity of acute lung injury.…”
Section: Hdaci Treatment In 2-hit Modelsmentioning
confidence: 53%
“…Importantly, these results were achieved in the absence of standard fluid resuscitation. Similar benefits were seen in a “two-hit” models, where hemorrhage was followed by a CLP insult in rodents (56). In that study, rats treated with VPA showed a significantly better long-term survival rate (86% vs. 14%, p < 0.05) (Figure 3a), suppressed inflammatory profile (Figure 3b), and lower severity of acute lung injury.…”
Section: Hdaci Treatment In 2-hit Modelsmentioning
confidence: 53%
“…Preclinical data have confirmed that treatment with a pan-HDACI agent (e.g. valproic acid) improves survival in small and large animal models of HS, suppresses inflammation, activates pro-survival pathways, attenuates tissue damage, prevents distant organ injury, and prevents death in models of septic shock as well as in two-hit rodent models [8, 1820]. Although pan HDACI are effective, they often require very large doses to exert the desired effect, which raises concerns about potential toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…VPA). While VPA has been shown to suppress inflammation, attenuate tissue damage, prevent distant organ injury, and death in models of septic shock as well as two-hit insults [8, 18], the non-specific inhibition of HDAC can be problematic. VPA inhibits class I (HDAC 1, 2, 3 and 8) and class II HDACs (HDAC4, 5 7, and 9) [25], which can have undesirable effects.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations